SISTEM MANAJEMEN MUTU ISO 21001: 2018 SEBAGAI STRATEGI PENINGKATAN KUALITAS PENDIDIKAN DI ERA REVOLUSI INDUSTRI 4.0 - Kusumawati, Niluh Ari (Jurnal Penjaminan Mutu, 2023)
The role of education in the era of "industrial revolution 4.0 is becoming increasingly important. Education must be able to prepare the younger generation to be capable of rapidly adapting to technological developments and also to produce creative, innovative, and critical-thinking human resources. In the era of the Industrial Revolution 4.0, ISO 21001:2018 quality management is becoming increasingly important as technology and digitalization increasingly affect learning and teaching. Education and training are no longer limited to physical classes but can also be done online and remotely. In the era of the Industry 4.0 revolution, organizations that want to survive in the global market must improve their quality management. The use of international quality management ISO 21001:2018 is the right choice, as it helps ensure organizations operate in accordance with international standards and provides great benefits to organizations. With ISO 21001:2018 quality management, education and training organizations can ensure that they remain relevant in the era of the Industrial Revolution 4.0 and provide quality services to customers. In implementing ISO 2100:2018, educational organizations need to pay attention to speed and flexibility in responding to change, as well as building a strong culture of innovation within the organization. In addition, the implementation of ISO 21001:2018 in the era of the Industrial Revolution 4.0 also requires a better integration between quality management systems and digital technologies.